Zulfiya’s Artistic Mastery As Exemplified In Her Poems And Publicistic Articles - Yusupova Mamura (International Journal Of Literature And Languages, 2025)
This article discusses the lyrics of Zulfiya, People’s Poet of Uzbekistan, as well as her editorial activity and publicistic mastery. First, the poet’s work in the publishing sphere is examined. The journal Saodat (formerly called Uzbekistan Women), where Zulfiya worked for many years as editor-in-chief, its orientation, the topics covered in it, the influence of the era, and the articles telling about the lives of progressive and active women are analyzed. In particular, Zulfiya’s articles calling on women to be active and encouraging them to take their place in social life are examined. Commentary is given on the articles published on the pages of the journal in 1961.